Landslide Risk Assessment Using a Geomorphological Approach: A Case Study of the Kelkit River Valley Downstream - Mehmet Emin Cihangir (Coğrafya Dergisi)
Sharp lithological transitions, high topographic features, and climatic and tectonic features cause periodic landslides downstream of the Kelkit Creek Valley. Thus, the hazards and risks of landslides in the area were evaluated using a geomorphological approach to reduce the losses that may occur therein. It was determined that 462 landslides in the study area were distributed according to certain topographic features and lithologies. The landslides were triggered by rapid snow melting in the upper parts of the valley in the north and by paleo-landslide topography and precipitation in the south. The morphological evolution and spatial persistence of areas with high landslide activity were interpreted from very-high-resolution to high-resolution satellite images (1and 5 m) and stereo aerial photos (1:16,000–1:35,000 scale) between 1958 and 2021. The landslide activities showed temporal and spatial differences with multitemporary landslide inventories determined using geographic information system and uncertainty analysis tools. Risks were evaluated according to the physical, social, systemic, and economic vulnerabilities in four regions with high activity and elements of risk. It was determined that the population and settlement densified during periods when landslide hazards increased. The risk elements and therefore the risk levels were high in the northwestern and southern parts of Koyulhisar and in the accumulation zone of the Sugozu, Gokdere, and Boyalı landslides.